Long-ranged dynamic magnetic interaction through low-dimensional systems - FERREIRA, MAURO (American Physical Society, 2008)
Magnetic units attached to low-dimensional metallic nanowires are known to interact via the conduction electrons of the wire leading to preferential alignment directions of the respective magnetic moments. In addition to this so-called static interaction, here we show that a very long-ranged interaction arises when these units are allowed to precess. This dynamic version of the magnetic interaction governs the spin dynamics of the magnetic moments. We are able to relate this interaction to the spin excitation spectrum of the system in which we establish a clear correspondence between the precession relaxation time and the features of the spin susceptibility. We show that the relaxation time is predominantly determined by the availability of noncoherent Stoner modes, a process analogous to Landau damping of plasmons in the electron gas. Contrary to expectations, our results indicate that the range of this interaction is robust against the introduction of disorder. Furthermore, we show that the interaction range is frequency dependent suggesting that it may be tunable by an adequate choice of excitation frequencies. We argue that this may pave the way to controlling the communication between distant parts of a spintronic device.
PUBLISHED
Keywords: magnetic moments; magnetic relaxation; magnetic susceptibility; nanowires; plasmons; spin dynamics